Motivasi Guru dalam Pemanfaatan Teknologi Artificial Intelligence (AI) untuk Meningkatkan Kualitas Pembelajaran Mata Pelajaran IPA di SMK PGRI Lubuklinggau - Fiqih Brian Karlingga; Satinem; Wahidin (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to describe teachers' motivation in utilizing Artificial Intelligence (AI) technology and to analyze its implications for improving the quality of science learning in SMK PGRI Lubuklinggau. The method used in this research is a qualitative approach with a descriptive design. The research subjects were ten science teachers at SMK PGRI Lubuklinggau who have utilized Artificial Intelligence (AI) technology in the learning process, including the stages of planning, implementation, and evaluation of learning. Data were collected through in-depth interviews, classroom observations, and documentation of science teachers who have implemented AI in their teaching practices. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that both intrinsic and extrinsic teacher motivation play an important role in encouraging the effective use of AI in learning. Teachers with high motivation tend to be more innovative, adaptive, and capable of utilizing AI to support learning planning, implementation, and evaluation. The use of AI also contributes to increased student engagement, learning effectiveness, and the quality of interaction between teachers and students. In conclusion, enhancing teacher motivation is a key factor in optimizing the use of AI to improve the quality of science learning in vocational high schools.   Keywords: Artificial Intelligence, learning quality, science learning, teacher motivation, vocational high school